Romosozumab (sclerostin monoclonal antibody) versus teriparatide in postmenopausal women with osteoporosis transitioning from oral bisphosphonate therapy: a randomised, open-label, phase 3 trial - Langdahl, Bente L.; Libanati, Cesar; Crittenden, Daria B.; Bolognese, Michael A.; Brown, Jacques P.; Daizadeh, Nadia S.; Dokoupilova, Eva; Engelke, Klaus; Finkelstein, Joel S.; Genant, Harry K.; Goemaere, Stefan; Hyldstrup, Lars; et al. (Lancet, 2017)
BACKGROUND: Previous bisphosphonate treatment attenuates the bone-forming effect of teriparatide. We compared the effects of 12 months of romosozumab (AMG 785), a sclerostin monoclonal antibody, versus teriparatide on bone mineral density (BMD) in women with postmenopausal osteoporosis transitioning from bisphosphonate therapy. METHODS: This randomised, phase 3, open-label, active-controlled study was done at 46 sites in North America, Latin America, and Europe. We enrolled women (aged ≥55 to ≤90 years) with postmenopausal osteoporosis who had taken an oral bisphosphonate for at least 3 years before screening and alendronate the year before screening; an areal BMD T score of -2·5 or lower at the total hip, femoral neck, or lumbar spine; and a history of fracture. Patients were randomly assigned (1:1) via an interactive voice response system to receive subcutaneous romosozumab (210 mg once monthly) or subcutaneous teriparatide (20 μg once daily). The primary endpoint was percentage change from baseline in areal BMD by dual-energy x-ray absorptiometry at the total hip through month 12 (mean of months 6 and 12), which used a linear mixed effects model for repeated measures and represented the mean treatment effect at months 6 and 12. All randomised patients with a baseline measurement and at least one post-baseline measurement were included in the efficacy analysis. This trial is registered with ClinicalTrials.gov, number NCT01796301. FINDINGS: Between Jan 31, 2013, and April 29, 2014, 436 patients were randomly assigned to romosozumab (n=218) or teriparatide (n=218). 206 patients in the romosozumab group and 209 in the teriparatide group were included in the primary efficacy analysis. Through 12 months, the mean percentage change from baseline in total hip areal BMD was 2·6% (95% CI 2·2 to 3·0) in the romosozumab group and -0·6% (-1·0 to -0·2) in the teriparatide group; difference 3·2% (95% CI 2·7 to 3·8; p<0·0001). The frequency of adverse events was generally balanced between treatment groups. The most frequently reported adverse events were nasopharyngitis (28 [13%] of 218 in the romosozumab group vs 22 [10%] of 214 in the teriparatide group), hypercalcaemia (two [<1%] vs 22 [10%]), and arthralgia (22 [10%] vs 13 [6%]). Serious adverse events were reported in 17 (8%) patients on romosozumab and in 23 (11%) on teriparatide; none were judged treatment related. There were six (3%) patients in the romosozumab group compared with 12 (6%) in the teriparatide group with adverse events leading to investigational product withdrawal. INTERPRETATION: Transition to a bone-forming agent is common practice in patients treated with bisphosphonates, such as those who fracture while on therapy. In such patients, romosozumab led to gains in hip BMD that were not observed with teriparatide. These data could inform clinical decisions for patients at high risk of fracture. FUNDING: Amgen, Astellas, and UCB Pharma.
EVALuna2:33272